The Causality Relationship Between Food Prices, Housing Prices and Exchange Rate in Türkiye - Turaboğlu, Tuncay Turan; Yılmaz, Ayşegül (International Journal of Economics and Financial Issues, 2025)
This study aims to examine the causality relationship between food prices, housing prices, and exchange rates in Turkiye. To this end, the Consumer Price Index (CPI) calculated for monthly food and non-alcoholic beverages, the Borsa Istanbul Construction Sector Index (XINSA), Housing Price Index (KFE), and exchange rate (USD-EURO) (KUR) data for the period March 2013 to March 2024 were analysed using the Granger Causality Test. According to the findings obtained from the analysis, a two-way causality relationship was found between the exchange rate (KUR) and the housing price index (LNKFE), as well as between the consumer price index (LNTUFE) calculated for food and non-alcoholic beverages and the construction sector index (LNXINSA). Similarly, there is a one-way causality relationship from the consumer price index for food and non-alcoholic beverages (LNTUFE) to the housing price index (LNKFE) and from the exchange rate (KUR) to the consumer price index for food and non-alcoholic beverages (TÜFE).